Which misspecifications persist? - Drew Fudenberg; Giacomo Lanzani (Theoretical Economics, 2023)
We use an evolutionary model to determine which misperceptions can persist. Every period, a new generation of agents use their subjective models and the data generated by the previous generation to update their beliefs, and models that induce better actions become more prevalent. An equilibrium can resist mutations that lead agents to use a model that better fits the equilibrium data but induce the mutated agents to take an action with lower payoffs. We characterize which steady states resist mutations to a nearby model, and which resist mutations that drop a qualitative restriction such as independence.
Keywords: C73; D83; 330; Berk-Nash equilibrium; evolution; Misspecified learning; payoff monotone dynamics